Mainstream Media Recirculation of Trust-Reducing Social Media Messages. Issue 2 (March 2022) - Christensen, Devin J.; Lovett, John; Curiel, John A.
Citizens need to trust in the integrity of news reporting for the free press to fulfill its role as a democratic institution that enables citizens to hold representatives accountable. Growing research has shown that increased use of social media erodes trust in legacy news. However, trust-reducing social media messages are not contained to social media platforms; they are widely recirculated by the mainstream media. We argue that mainstream media corporations select social media messages to recirculate precisely because of their trust-reducing features in order to respond to short-term competitive market incentives. We turn to Donald Trump's Twitter posts as examples of trust-reducing messages and show that the media cites more trust-reducing messages more quickly and more frequently than less trust-reducing messages. These findings implicate mainstream media corporations alongside social media platforms in the systematic and ongoing degradation of trust in legacy news reporting.